Design of CMOS High Linear Low Noise Amplifier for Small Satellite Ground Station - Malleswari, M.; Manjula, S. (International Journal of Engineering and Technology, 2018)
Ground stations are established to provide communication with the satellite.Â The quality of communication depends on the performance of satellite ground station in addition to that of satellite. If the ground station is implemented in urban areas, intermodulation interferences affect the front end of the ground station. The non-linearity of low noise amplifier (LNA) is disturbed by these intermodulation products. In ground station, linearity is more important factor in the design of LNA. In this paper, LNA is designed at S band using CMOS technology. Modified derivative superposition (MDS) linearization technique is incorporated in LNA. The performance of high linear CMOS LNA is analyzed with the linearization techniques. This linear LNA is designed using 90 nm CMOS technology that provides good IIP3 value of 5 dBm, 17.7 dB gain, 1.1 dB NF and 5.79 mW power consumption.Â